Assessment of Plasmodium falciparum drug resistance molecular markers from the Blue Nile State, Southeast Sudan - Mohamed, Abdelrahim O. (Malar J, 2020)
BACKGROUND: Plasmodium falciparum malaria is a public health problem worldwide. Malaria treatment policy has faced periodic changes due to emergence of drug resistant parasites. In Sudan chloroquine has been replaced by artesunate and sulfadoxine/pyrimethamine (AS/SP) in 2005 and to artemether–lumefantrine (AL) in 2017, due to the development of drug resistance. Different molecular markers have been used to monitor the status of drug resistant P. falciparum. This study aimed to determine the frequency of malaria drug resistance molecular markers in Southeast Sudan. METHODS: The samples of this study were day zero dried blood spot samples collected from efficacy studies in the Blue Nile State from November 2015 to January 2016. A total of 130 samples were amplified and sequenced using illumina Miseq platform. The molecular markers included were Pfcrt, Pfmdr1, Pfdhfr, Pfdhps, Pfk13, exonuclease and artemisinin resistant (ART‐R) genetic background (Pfmdr2, ferroredoxine, Pfcrt and Pfarps10). RESULTS: Resistance markers for chloroquine were detected in 25.8% of the samples as mutant haplotype Pfcrt 72-76 CVIET and 21.7% Pfmdr1 86Y. Pfdhfr mutations were detected in codons 51, 59 and 108. The ICNI double-mutant haplotype was the most prevalent (69%). Pfdhps mutations were detected in codons 436, 437, 540, 581 and 613. The SGEGA triple-mutant haplotype was the most prevalent (43%). In Pfdhfr/Pfdhps combined mutation, quintuple mutation ICNI/SGEGA is the most frequent one (29%). Six of the seven treatment failure samples had quintuple mutation and the seventh was quadruple. This was significantly higher from the adequately responsive group (P < 0.01). Pfk13 novel mutations were found in 7 (8.8%) samples, which were not linked to artemisinin resistance. Mutations in ART‐R genetic background genes ranged from zero to 7%. Exonuclease mutation was not detected. CONCLUSION: In this study, moderate resistance to chloroquine and high resistance to SP was observed. Novel mutations of Pfk13 gene not linked to treatment failure were described. There was no resistance to piperaquine the partner drug of dihydroartemisinin/piperaquine (DHA-PPQ).